Voxel-based edge bundling through direction-aware kernel smoothing. (October 2019) - Zielasko, Daniel; Zhao, Xiaoqing; Demiralp, Ali Can; Kuhlen, Torsten W.; Weyers, Benjamin
Highlights: The 10k edges represented in 10k voxels still allow for an interactive analysis. Directed and undirected networks are supported. Explicit bundle generation enables arbitrary rendering styles and targets. Graphical abstract: Abstract: Relational data with a spatial embedding and depicted as node-link diagram is very common, e.g, in neuroscience, and edge bundling is one way to increase its readability or reveal hidden structures. This article presents a 3D extension to kernel density estimation-based edge bundling that is meant to be used in an interactive immersive analysis setting. This extension adds awareness of the edges' direction when using kernel smoothing and thus implicitly supports both directed and undirected graphs. The method generates explicit bundles of edges, which can be analyzed and visualized individually and as sufficient as possible for a given application context, while it scales linearly with the input size.